Using organizational performance assessment to improve service to the community. (15th January 2021) - McIntyre, Michael L.; Caputo, Tullio; Hodgkinson, Tarah; Wang, Lucy; Davidson, Robert
ABSTRACT: In this paper, we present the results of a case study of an innovative organizational performance assessment approach implemented within a specialty unit of a large Canadian police service. The CIV Tool (Capability, Importance and Value) was used in the case study to identify opportunities for enhancing the unit's performance. The CIV Tool is based on an action research methodology that focuses attention on police roles and the value these provide to stakeholders. Information garnered through the use of the CIV Tool is intended to inform actionable changes. Its use helped unit supervisors identify issues around role creep and role relevance. Working closely with team members, supervisors made changes to operating practices within the unit resulting in an increase in the services provided, a significant reduction in repeat calls for service and a positive response by unit members. These results were achieved within the existing budget and staffing levels at a time when the organization was experiencing significant budgetary challenges. These findings suggest that using the CIV Tool can provide important insights into police organizational performance that can be used for continuous organizational improvement which can enhance service delivery and employee engagement.